Formative Feedback and Collaborative Work in the Meaningful Learning of Basic Science Items (LACCEI, 2024)
This research describes the experience of the application of a formative feedback plan in students of the IV semester of the subject of Mathematical Analysis II of the Academic School of Civil Engineering of the National Intercultural University of Quillabamba - Peru (UNIQ ), students of the IV semester of the Differential Equations subject of the Academic School of Electrical Engineering of the National University San Antonio Abad of Cusco-Peru (UNSAAC), students of the II semester of the Calculus II subject of the Academic School of Engineering Environment of the National University of Moquegua José Carlos Mariátegui-Perú (UNAM), students of the III semester of Statistics and Probability of Civil Engineering of the National University Micaela Bastidas of Apurímac-Perú (UNAMBA), students of the IV semester of the Physics subject I of the Academic School of Civil Engineering of the National Intercultural University of Quillabamba - Peru ( UNIQ) and in students of the V semester of the subject of Electrical Circuits I of the Mechatronic Engineering study program of the Catholic University of Santa María Arequipa-Perú (UCSM). At first, a diagnostic evaluation of the learning levels necessary for the corresponding curricular readjustment was put into practice. In all cases, the results were negative and of a very low level compared to the results obtained in the same subjects before social isolation as a result of the COVID-19 pandemic, making it necessary to implement a dosed feedback plan and that mitigates the negative effects of virtual education and strengthens their previous knowledge to build their new learning in a significant way. This work was carried out in the 2022-II semester, immediately after having resumed face-to-face academic activities and prior coordination between teachers and students of the times and work spaces outside the hours determined for the development of each subject. During the execution of the plan, the permanent evaluation was applied through an observation sheet that allowed timely and effective feedback, managing to meet the learning needs of each student. After the application, an exit evaluation was carried out considering all the topics covered. Unlike what was previously described, this time the results were quantitatively and qualitatively satisfactory. Additionally, having implemented this plan in different universities provides relevant information on the goodness of face-to-face education compared to virtual education, specifically, in subjects with basic science topics, taking into account that during the period of social isolation, tools were used. technologies to mediate learning whose results were not encouraging. After this experience, he wishes to continue strengthening a feedback system that is not reduced to the elementary and descriptive favoring the reflection that allows quality autonomous learning as well as self-determination by future engineering professionals. In the same way, the collegiate work between university professors must be strengthened and recognized institutionally.